2019
DOI: 10.1002/pros.23824
|View full text |Cite
|
Sign up to set email alerts
|

Association among plasma 1,25(OH)2D, ratio of 1,25(OH)2D to 25(OH)D, and prostate cancer aggressiveness

Abstract: Background African‐American (AA) men tend to present with more aggressive prostate cancer (Gleason score >7) than European‐American (EA) men. Vitamin D and its metabolites are implicated in prostate cancer biology with vitamin D deficiency, indicated by its metabolite levels in serum or plasma, usually observed in AA men. Objective To determine if 1, 25‐dihydroxy vitamin D3 [1,25(OH) 2 D] plasma levels in AA and EA prostate cancer patients alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The relationship between vitamin D dysregulation and aggressive disease is supported by rodent models, where prostatic VDR deletion within the TgAPT mouse model of prostate carcinogenesis increased adenocarcinoma foci number and area (Fleet et al, 2019). The relationship is also observed in patients, where vitamin D deficiency is associated with risk of aggressive PCa (Fang et al, 2011;Giovannucci et al, 2006;Murphy et al, 2014;Ramakrishnan et al, 2019;Studzinski and Moore, 1995). Vitamin D deficiency is especially pertinent to PCa patients who are frequently deficient due to high skin melanin content, such as African Americans, (Murphy et al, 2014) or lack of sun exposure (Gilbert et al, 2009), such as the elderly (Elshazly et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…The relationship between vitamin D dysregulation and aggressive disease is supported by rodent models, where prostatic VDR deletion within the TgAPT mouse model of prostate carcinogenesis increased adenocarcinoma foci number and area (Fleet et al, 2019). The relationship is also observed in patients, where vitamin D deficiency is associated with risk of aggressive PCa (Fang et al, 2011;Giovannucci et al, 2006;Murphy et al, 2014;Ramakrishnan et al, 2019;Studzinski and Moore, 1995). Vitamin D deficiency is especially pertinent to PCa patients who are frequently deficient due to high skin melanin content, such as African Americans, (Murphy et al, 2014) or lack of sun exposure (Gilbert et al, 2009), such as the elderly (Elshazly et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…The relationship between vitamin D and prostate cancer risk is still controversial, due to contradictory data reporting an inverse correlation [62,73,76,79,96], or a direct correlation [78,97], or even the absence of any correlation [74,75,77] between 25(OH)D levels and prostate cancer. Interestingly, a recent meta-analysis of 21 observational studies suggests a negative role of vitamin D in prostate cancer, by reporting a direct correlation between high 25(OH)D levels and prostate cancer risk (OR: 1.17, 95% CI: 1.05 to 1.30, p = 0.004), therefore inviting to caution in vitamin D supplementation [97].…”
Section: Vitamin D and Cancer: Epidemiological Evidencementioning
confidence: 99%
“…Several observational studies have shown that circulating levels of 25(OH)D, used as surrogate marker for the evaluation of vitamin D status, may be associated with cancer risk [ 5 , 6 , 56 , 57 , 58 , 59 ] and prognosis [ 6 , 60 , 61 , 62 , 63 , 64 , 65 ]. A strong association between low 25(OH)D circulating levels and colorectal [ 6 , 56 , 60 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], prostate [ 59 , 62 , 63 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ] and breast [ 52 , 58 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ] cancer risk has been reported.…”
Section: Vitamin D and Cancer: Epidemiological Evidencementioning
confidence: 99%
“…Furthermore, Findlay et al showed that 1α,25(OH)2D3 enhanced radiation sensitivity in colorectal cancer cells through regulating the EMT [42]. Higher plasma levels of 25(OH)D3 are associated with a decreased risk of highly aggressive prostate cancer [43]. Mutation or deficiency of the genes and enzymes responsible for the transport or metabolism of 25(OH)D3 may alter its levels and functions [43].…”
Section: Introductionmentioning
confidence: 99%
“…Higher plasma levels of 25(OH)D3 are associated with a decreased risk of highly aggressive prostate cancer [43]. Mutation or deficiency of the genes and enzymes responsible for the transport or metabolism of 25(OH)D3 may alter its levels and functions [43]. For instance, a mutation in CYP2R1, a key hydroxylase for 25(OH)D3 production, resulted in deficiency thereof, as well as symptoms of vitamin D-dependent rickets [44].…”
Section: Introductionmentioning
confidence: 99%